Tuning Modern Pedagogy to the Rhythm of Indonesian Music Tradition - Aryandari, Citra (FKIP Universitas Lampung, 2024)
Tuning Modern Pedagogy to the Rhythm of Indonesian Music Tradition. This research explores the critical intersection of traditional Indonesian music and the modern education system, delving into the complex challenges and innovative strategies for musical heritage preservation. Employing a comprehensive qualitative case study approach, the study investigates music education practices across various Indonesian educational institutions through meticulous archival research, in-depth expert interviews, and direct observational methodologies. The investigation reveals significant challenges confronting traditional music education, most notably the pervasive influence of Western pop music that has substantially diminished youth interest in indigenous musical forms. Despite these substantial obstacles, the research uncovers promising integration models, such as adaptive approaches to the traditional guru-cantrik teaching system and implementation of collaborative, communal learning strategies. Pedagogical innovations emerge as a crucial mechanism for preserving and transmitting traditional musical knowledge. These innovations include developing hybrid curricula that bridge traditional and contemporary musical education, creating innovative digital notation systems, and establishing online learning platforms that extend the reach of traditional musical instruction. The research critically highlights the delicate balance required between technological advancement and the preservation of traditional musical values. The findings suggest that the integration models developed within the Indonesian context could serve as a valuable international reference for countries seeking to modernize music education while simultaneously maintaining and revitalizing their unique musical heritage. By demonstrating the potential for strategic educational approaches to breathe new life into traditional music, this study provides important insights into cultural preservation, educational innovation, and the dynamic relationship between tradition and modernity in musical education. Keywords: traditional Indonesian music, modern music education, integration models, pedagogical innovation, cultural preservation.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024132